An Evaluation of Gamified Training: Using Narrative to Improve Reactions and Learning. (August 2017) - Armstrong, Michael B.; Landers, Richard N.
Background and Aim. Gamification is growing in popularity ineducation and workplacetraining, but it is unclear whichgame elements are conducive tolearning . Thetheory of gamified learning suggests that one type of gamification, the addition ofgame fiction/narrative, can be used to improve learning outcomes, and theTechnology-Enhanced Training Effectiveness Model (TETEM) suggests individual differences impact the strength of this effect. From this theoretical basis, this study gamified a training module with game fiction in order to improve outcomes over the original training. Results and Conclusion. In a study of 273 learners, trainees were significantlymore satisfied with training enhanced with game fiction over the control text ( d = 0.65) butdid not differ indeclarative knowledge scores by condition. Further, trainees in the control conditionscored higher onprocedural knowledge than trainees in the game fiction condition, although the effect was smaller ( d = −0.40). Thus, the use of narrativeimproved reactions to training but at some cost to training effectiveness.Attitudes toward game-based learning were also tested as a moderator of the condition-outcome relationship.